Power Shifting Global Politics From The European Union (EU) To The Shanghai Cooperation Organization (SCO): Analysis A Critical Analysis of The Russian-Ukrainian War - Afriyanto Putra, Fandy; Drajati Nugrahani, Henny Saptatia; Agus Yogiswara, I Made; Anas Arifin, Muhammad (Pelopor Publikasi Akademika, 2024)
This research discusses the shift in global political dynamics from the European Union (EU) to the Shanghai Coopertation Organization (SCO) as a result of the Russia-Ukraine conflict. Over the years, the EU has been a significant global power, however, the Ukraine conflict has weakened its influence. This event became an important driver of the shift in political power, with the SCO emerging as one of the main players in response. A mixed research method is used, involving a multidisciplinary approach and critical analysis covering geopolitics, security, and international politics. The Regional Security Complex and Structural Power theories provide the theoretical foundation for this analysis. The results show that the Ukraine conflict has weakened the EU's global influence by exposing internal divisions in response to the conflict. The EU imposed economic sanctions on Russia in response to its annexation of Crimea and support for the insurgency in eastern Ukraine. However, the EU has also been active in diplomacy and mediation to find a political solution. Meanwhile, the SCO is emerging as a new force in global politics with a regional cooperation platform that is increasingly visible at the international level. The shift to the SCO could have a major impact on global political and security dynamics. This potential is driven by the SCO's large member population and the EU's internal problems. If the focus shifts to the SCO, it could shift the center of policy and diplomacy from Europe to Asia, creating a new paradigm in international relations. The SCO's growing influence could give Asian countries, especially SCO members, more of a role in shaping global policy.